Aqueous Extract from Pepino (Solanum muricatum Ait.) Attenuated Hyperlipidemia and Cardiac Oxidative Stress in Diabetic Mice. (8th July 2012) - Wang, Zhi-hong; Hsu, Cheng-chin; Yin, Mei-chin
Abstract : This study examined the lipid-lowering and cardiac protective effects of aqueous extract of pepino ( Solanum muricatum Ait.) in type 2 diabetic mice. Pepino at 1, 2, or 5% was supplied for 8 weeks. Results showed that pepino significantly decreased water intake and epididymal fat pad weight in diabetic mice (P < 0.05 ). Pepino treatments also significantly reduced plasma glucose and insulin levels, HOMA-IR index, and improved oral glucose tolerance (P < 0.05 ). Plasma and hepatic levels of triglyceride and total cholesterol (TC) were higher in diabetic groups when compared with normal group (P < 0.05 ), pepino treatments at 2 and 5% decreased triglyceride and TC levels in both plasma and liver (P < 0.05 ). Diabetes enhanced mRNA expression of resistin and diacylglycerol acyltransferase1 (DGAT1) in epididymal fat pad (P < 0.05 ); however, pepino intake significantly suppressed mRNA expression of resistin and DGAT1 in epididymal fat pad (P < 0.05 ). Pepino intake significantly reduced reactive oxygen species level, increased glutathione level, and retained glutathione peroxidase and catalase activities in cardiac tissues (P < 0.05 ). These findings suggest that pepino could be considered as a functional food for the alleviation of type 2 diabetes.